Novel Role of Endothelial Derived Exosomal HSPA12B in Regulating Macrophage Inflammatory Responses in Polymicrobial Sepsis - Tu, Fei; Wang, Xiaohui; Zhang, Xia; Ha, Tuanzhu; Wang, Yana; Fan, Min; Yang, Kun; Gill, P. Spencer; Ozment, Tammy R.; Dai, Yuan; Liu, Li; Williams, David L.; et al. (Frontiers in Immunology, 2020)
Endothelial cell dysfunction contributes to sepsis induced initiate immune response and the infiltration of immune cells into organs, resulting in organ injury. Heat shock protein A12B (HSPA12B) is predominantly expressed in endothelial cells. The present study investigated whether endothelial HSPA12B could regulate macrophage pro-inflammatory response during sepsis. Wild type (WT) and endothelial cell-specific HSPA12B deficient (HSPA12B–/–) mice were subjected to CLP sepsis. Mortality and cardiac function were monitored. Higher mortality, worsened cardiac dysfunction, and greater infiltrated macrophages in the myocardium and spleen were observed in HSPA12B–/– septic mice compared with the WT septic mice. The serum levels of TNF-α and IL-1β were higher and the levels of IL-10 were lower in HSPA12B–/– septic mice than in WT septic mice. Importantly, endothelial exosomes contain HSPA12B which can be uptaken by macrophages. Interestingly, endothelial exosomal HSPA12B significantly increases IL-10 levels and decreases TNF-α and IL-1β production in LPS-stimulated macrophages. Mechanistic studies show that endothelial exosomal HSPA12B downregulates NF-κB activation and nuclear translocation in LPS stimulated macrophages. These data suggest that endothelial HSPA12B plays a novel role in the regulation of macrophage pro-inflammatory response via exosomes during sepsis and that sepsis induced cardiomyopathy and mortality are associated with endothelial cell deficiency of HSPA12B.